Muscle ultrasound: A useful tool in newborn screening for infantile onset pompe disease. Issue 44 (November 2017) - Hwang, Hsuen-En; Hsu, Ting-Rong; Lee, Yueh-Hui; Wang, Hsin-Kai; Chiou, Hong-Jen; Niu, Dau-Ming
Abstract : Abstract: Our study aimed to evaluate the utility of muscle ultrasound in newborn screening of infantile-onset Pompe disease (IOPD) and to establish a system of severity grading. We retrospectively selected 35 patients with initial low acid alpha-glucosidase (GAA) activity and collected data including muscle ultrasound features, GAA gene mutation, activity/performance, and pathological and laboratory findings. The echogenicity of 6 muscles (the bilateral vastus intermedius, rectus femoris, and sartorius muscles) was compared to that of epimysium on ultrasound and rated either 1 (normal), 2 (mildly increased), or 3 (obviously increased). These grades were used to divide patients into 3 groups. IOPD was present in none of the grade-1 patients, 5 of 9 grade-2 patients, and 5 of 5 grade-3 patients ( P < .001). Comparing grade-2 plus grade-3 patients to grade-1 patients, muscle ultrasound detected IOPD with a sensitivity and specificity of 100.0% (95% confidence interval [CI]: 69.2%–100%) and 84.0% (95% CI: 63.9%–95.5%), respectively. The mean number of affected muscles was larger in grade-3 patients than in grade-2 patients (4.2 vs. 2.0, P = .005). Mean alanine transaminase (ALT), aspartate transaminase (AST), creatine kinase (CK), and lactate dehydrogenase (LDH) levels were differed significantly different between grade-3 and grade-1 patients ( P < .001). Because it permits direct visualization of injured muscles, muscle ultrasound can be used to screen for IOPD. Our echogenicity grades of muscle injury also correlate well with serum levels of muscle-injury biochemical markers.